Challenge to patenting neem processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Two hundred organizations from 35 countries supported the Foundation for Economic Trends, based in Washington DC, when it filed its legal challenge against the giant seed company W R Grace. The dispute is over a patent held by the seed company and...